(untitled) (Research, Society and Development, 2020)
Soy is a highly nutritious food because it contains proteins, vitamins, minerals and fibers, so this legume has an important role in human and animal nutrition. With that, the objective of this work was to investigate the effect of different doses of organomineral and triple superphosphate in response to plant height, dry matter of the aerial part, productivity and leaf phosphorus content in soybean culture. The experiment was carried out in the city of Rio Verde - GO, in a soil classified as medium texture Red Latosol. The experimental design adopted was a randomized block design with four replications, analyzed in a double factorial scheme, and the treatments comprised five doses. (0, 50, 100, 150 and 200 kg ha-1) from two fertilizer sources (triple and organomineral superphosphate). The plant height (m), dry mass of the aerial part (g plant-1), productivity (kg ha-1) and leaf phosphorus content (dag kg-1) were analyzed. The sources of fertilizers provided a statistical difference for the plant height, regardless of the doses, while leaf phosphorus content, productivity and dry mass of the aerial part did not show any difference to this source of variation. With this it was concluded that the variables, plant height, leaf phosphorus content and grain yield of the soybean cultivar experimented, are increased with the increase of the doses of organomineral and mineral fertilizer and that for the experimental conditions of this research, if it is stated that the orgnomineral can totally replace the triple superphosphate mineral fertilizer.